The Impact of Shift Work-Related Circadian Rhythm Disruption on Inflammatory Biomarkers - Suyagh, Maysa; Alefishat, Eman; Abu Farha, Rana; Akour, Amal; Kasabri, Violet; Bulatova, Nailya (Jordan Journal of Pharmaceutical Sciences, 2018)
OBJECTIVE: This study aimed to examine the effect of circadian rhythm disruption in night-shift workers on systemic biomarkers of inflammation. METHODS Demographic data, clinical parameters and data on working patterns of 126 adult employees were documented. Serum levels of biomarkers were measured by enzymatic assay procedures. RESULTS: Night-shift workers had markedly lower anti-inflammatory IL-10 and cardioprotective adiponectin and MCP-1 compared to daytime workers. Night-shift workers’ MIF, LAR, TNF-α and TNF-α/IL-10 ratio were significantly higher than those in day shift workers. Spearman’s correlation showed that MIF, TNF-α, LAR and TNF-α/IL-10 ratios were positively and significantly correlated with both the duration of the night shift and total number of shifts (p < 0.05). Meanwhile, IL-10, adiponectin and MCP-1 were negatively and significantly correlated with both variables (p < 0.05). CONCLUSION: Night shift work may be closely associated with a higher propensity of cardiometabolic risk factors clustering. Therefore, close monitoring of shift workers’ clinical status and lifestyle is warranted.